Transformasi Kepemimpinan dalam Manajemen Strategis di Era Digital : Tinjauan Literatur Review - Moh. Sofiyanto; Mochammad Isa Anshori; Nurita Andriani (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
Transformation leaders play an important role in directing the organizational transformation process, especially in integrating the stages of change into the new organizational culture. Management in the digital era emphasizes the use of digital technology to manage business operations and human resources, including the implementation of digital systems to improve operational efficiency, communication, and decision making. This research is a description with a qualitative approach that uses a literature review as a secondary data source to examine leadership transformation in strategic management in the digital era. The transformational leadership model highlights the importance of leaders in driving organizational focus, building trust, and improving performance. Leadership in the digital era demands value congruence, inspiration, empowerment, and simple strategies. Future leaders need to have creativity, good communication skills, the ability to manage failure, and the ability to lead innovation in a changing era